The Prevalence of glucose dysregulations (GDs) in patients with β-thalassemias in different countries: A preliminary ICET-A survey: Prevalence of glucose dysregulations (GDs) in patients with β-thalassemias - De Sanctis, Vincenzo; Soliman , Ashraf; Tzoulis, Ploutarchos; Daar, Shahina; Kattamis, Antonis; Delaporta , Polyxeni; Yassin, Mohamed A.; Karimi, Mehran; Canatan, Duran; Al Jaouni , Soad; Galati, Maria Concetta; Raiola, Giuseppe; et al. (Acta Biomedica Atenei Parmensis, 2021)
.